Faktor-Faktor yang Memengaruhi Niat Menggunakan Teknologi Virtual Try-On Produk Make-Up pada Gen Z - Pratiwi, Viyonila; Parlyna, Ryna; Usman, Osly (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the factors that influence behavioral intention in using virtual try-on (VTO) technology for makeup products. The variables tested in this study include perceived usefulness, perceived ease of use, social influence, and perceived trust. This study used a quantitative approach with an online survey method. Data were collected from 170 respondents who were Generation Z, domiciled in DKI Jakarta, and knew or had used the virtual try-on feature for makeup products. The sampling technique used was purposive sampling. Data were collected through an online questionnaire. The data analysis technique used was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach to test the relationship between variables in the research model. The results showed that perceived ease of use had a positive and significant effect on behavioral intention and perceived usefulness. In addition, social influence had a positive and significant effect on behavioral intention and perceived trust. Perceived trust was also shown to have a positive and significant effect on behavioral intention in using virtual try-on technology. However, perceived usefulness did not show a significant effect on behavioral intention. Furthermore, the test results show that perceived trust mediates the effect of social influence on behavioral intention, indicating that social influence can increase intention to use virtual try-on technology by building user trust. This study recommends that beauty brands focus their virtual try-on technology development on aspects of ease of use, increasing user trust, and leveraging social influence through digital media to increase usage interest among Generation Z.